Immunity Of The Advocate And Solicitor - Chen, Vivien JH (Journal of Malaysian and Comparative Law, 2003)
An advocate and solicitor owes a general duty of care to her client. This duty arises under the law of contract as well as tort. Once a client engages an advocate and solicitor to act on her behalf, the retainer of the advocate and solicitor by the client gives rise to a contractual relationship between the advocate and solicitor and the client. Consequently, an action based on contract may be brought by a client against an advocate and solicitor for failure to exercise due care in the conduct of the client’s case. Likewise, where an advocate and solicitor is engaged by a client, the law of torts impose a duty of care on the advocate and solicitor towards her client. The case of Hedley Byrne & Co Ltd v Heller & Partners Ltd indicates that a duty of care is imposed on persons exercising professional skills. Liability for negligence arises from a professional relationship where there has been a breach of duty of are by the professional. Nevertheless, it has been accepted that in certain limited situations an advoate and solicitor enjoys immunity from liability for negligence. Such immunity from liability was established in the landmark decision of Rondel v Worsley.